Skippyjon Jones snow what - Schachner, Judith Byron (New York : Dial Books for Young Readers, 2014)
Skippyjon Jones, the Siamese cat that thinks he is a Chihuahua dog, stars in a fairy tale set in the winter wonderland of his imagination.
3.7
K-3
Keywords: Siamese cat -- Juvenile fiction; Chihuahua (Dog breed) -- Juvenile fiction; Fairy tales; Siamese cat -- Fiction; Cats -- Fiction; Chihuahua (Dog breed) -- Fiction; Dogs -- Fiction; Fairy tales; Siamese cats -- Fiction; Cats -- Fiction; Chihuahuas (Dog breed) -- Fiction; Dogs -- Fiction; Fairy tales; Siamese cat -- Fiction; Cats -- Fiction; Chihuahua (Dog breed) -- Fiction; Dogs -- Fiction; Fairy tales -- Fiction; Fairy tales